2014
DOI: 10.1161/circep.114.001631
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Perimitral Flutter due to Vein of Marshall Epicardial Connections Bypassing the Mitral Isthmus

Abstract: A 68-year-old man with hypertension, dyslipidemia, obstructive sleep apnea, chronic obstructive pulmonary disease, sick sinus syndrome status post dual chamber pacemaker, and a history of 2 pulmonary vein isolation ablations for persistent atrial fibrillation was evaluated in our institution for recurrent atrial flutter.He underwent a complete electrophysiology study. A duodecapolar catheter was used, so that the distal 10 poles were inside the coronary sinus (CS) and the proximal were in the right atrium. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…The vein or ligament of Marshall, is an anatomical structure related to atrial tachyarrhythmia . The Marshall bundle is reported to be involved with complex atrial tachycardia (AT) by bridging endocardial activation . Ethanol infusion is one strategy to treat Marshall bundle‐related atrial tachycardia (MB‐AT) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vein or ligament of Marshall, is an anatomical structure related to atrial tachyarrhythmia . The Marshall bundle is reported to be involved with complex atrial tachycardia (AT) by bridging endocardial activation . Ethanol infusion is one strategy to treat Marshall bundle‐related atrial tachycardia (MB‐AT) .…”
Section: Introductionmentioning
confidence: 99%
“…The Marshall bundle is reported to be involved with complex atrial tachycardia (AT) by bridging endocardial activation . Ethanol infusion is one strategy to treat Marshall bundle‐related atrial tachycardia (MB‐AT) . Previous reports have suggested that the accessibility of the vein of Marshall (VOM) by an angiographic catheter is limited .…”
Section: Introductionmentioning
confidence: 99%
“…Although the relationship between the VOM and genesis of AF have been previously reported,3, 4 there have been reports of catheter ablation of recurrent ATs via the VOM after AF ablation in a few cases 5, 6, 7, 8. In many of the previous reports, it could be confirmed that the VOM was the origin of the arrhythmia or a part of the reentry circuit, by inserting a thin electrode catheter into the Marshall vein 6, 7.…”
Section: Discussionmentioning
confidence: 96%
“…This ablation method would be less invasive than any other method, and would therefore be useful. We also believed ablation at the anterior ridge of the PV or an ethanol injection would be useful 8 . However, in such a case with a thin and short VOM, we recommend that an ablation in a branch of the VOM from the CS should be preferentially selected for the ablation of an AT via the VOM.…”
Section: Discussionmentioning
confidence: 99%
“…The vein of Marshall has been postulated to harbor epicardial connections between the coronary sinus (CS) and the left atrium (LA), sustaining peri‐mitral flutters refractory to endocardial ablation 2,3 . Conduction across the intercaval bundle, which connects the right atrium to the right superior pulmonary vein, has been reported to render isolation of the RSPV challenging requiring ablation at the carina or from the RA 4,5 .…”
Section: Figurementioning
confidence: 99%